Parasitic Contamination of Commonly Consumed Fresh Leafy Vegetables in Benha, Egypt - Maysa Ahmad Eraky; Samia Mostafa Rashed; Mona El-Sayed Nasr; Azza Mohammed Salah El-Hamshary; Amera Salah El-Ghannam (Journal of Parasitology Research)
This study evaluated the degree of parasitic contamination of vegetables which are commercialized and consumed fresh in Benha, Egypt. It included 530 vegetables: lettuce, watercress, parsley, green onion, and leek. Vegetables were collected randomly from markets within Benha. Samples were washed in saline, and the resulting washing solution was filtered and centrifuged to concentrate the parasitic stages. Sediments and supernatants were examined by iodine and modified Ziehl-Neelsen stained smears. Intestinal parasites were detected in 157/530 (29.6%) samples. Giardia lamblia cysts were the most prevalent parasite (8.8%) followed by Entamoeba spp. cysts (6.8%), Enterobius vermicularis eggs (4.9%), various helminth larvae (3.6%), Hymenolepis nana eggs (2.8%), Hymenolepis diminuta eggs (2.1%), and Ascaris lumbricoides eggs (0.6%). The highest contaminated vegetable was lettuce (45.5%) followed by watercress (41.3%), parsley (34.3%), green onion (16.5%), and leek (10.7%). These results indicate a significant seasonal variation (P<0.05), with highest prevalence in summer (49%) and the lowest in winter (10.8%). These findings provide evidence for the high risk of acquiring parasitic infection from the consumption of raw vegetables in Benha, Egypt. Effective measures are necessary to reduce parasitic contamination of vegetables.